Formação política e práxis pedagógica dos professores do campo - Oliveira, Cybely Ribeiro de; Frota, Maria Joiciane Batista; Avila, Milena Aires de (Ensino em Perspectivas, 2021)
This work, financed by Funcap and CNPQ, aims to understand how a politically engaged formation contributes to the teaching praxis of teachers who are inserted in the field, articulated with a possible realization of emancipatory education. It is theoretically supported by classic Marxist authors such as Marx and Engels, as well as authors who mainly debate rural education such as Arroyo, Alencar and Caldart. As a result, it was possible to analyze that a formation articulated with social movements and based on dialectical historical materialism, provides concrete answers that are obtained by the subjects who are inserted in the field, and that is why they carry out a teaching praxis committed to society for combating of the capitalist structure.